IMPLEMENTASI KETERAMPILAN ABAD 21 DALAM PEMBELAJARAN BERBASIS MEDIA TEKNOLOGI INFORMASI DAN KOMUNIKASI DI SEKOLAH DASAR - Aviana, Dina; Nurhasanah, Ana; Pribadi, Reksa Adya (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
Twenty-first century learning prepares future generations to acquire the skills necessary for the modern era. In this learning process, information and communication technology (ICT) serves as a tool or media to achieve a learning process which emphasizes the 21st century skills students must develop, particularly through the implementation of ICT-based learning media. This study aims to investigate the utilization of ICT media in learning activities, the challenges in using ICT media during the learning process, and the 21st century skills outcomes of students after implementing ICT-based learning media. The research uses a qualitative approach with a descriptive method, collecting data in the form of words and images. The study involved 19 participants, consisting of one (1) school principal, two (2) fourth-grade teachers, and 16 fourth-grade students at SDIT Mumtaz Al-Bantani. The results indicate that the use of ICT-based learning media in educational activities has been effective, and the utilization of ICT media as a learning tool has successfully improved students' 21st century skills.